The impact of behavioral participation as a mediator for emotional involvement on viewers of K-Dramas' propensity to buy celebrity-related goods in Indonesia - Shafa Tasya Salsabila; Erni Masdupi (Marketing Management Studies, 2023)
The purpose of this study is to analyze the effect of emotional involvement and behavioral involvement on the purchase intention of celebrity-related products for K-Drama viewers in Indonesia. The population in this study were K-Drama viewers who had watched K-Drama at least 10 times and had never purchased celebrity-related products. There were 250 respondents who were sampled in this study. Data collection was carried out by sending questionnaires via Google Forms online. Data processing was carried out with Structural Equation Modeling (SEM) using IBM SPSS AMOS 24 software. This study shows the results that (1) emotional involvement has a positive and significant effect on behavioral involvement. (2) Emotional involvement has no positive and significant effect on the intention to purchase celebrity-related products. (3) Behavioral involvement has a positive and significant effect on the intention to purchase celebrity-related products. (4) Behavioral involvement mediates the relationship between emotional involvement and intention to purchase celebrity-related products.